Hepatoprotective potential of a novel quinazoline derivative in thioacetamide-induced liver toxicity - Suzy Salama; Chin Siang Kue; Haryanti Mohamad; Fatima Omer; Mohamed Yousif Ibrahim; Mohamed Yousif Ibrahim; Mahmood Abdulla; Hapipah Ali; Abdalbasit Mariod; Abdalbasit Mariod; Soher Nagi Jayash (Frontiers Media S.A., 2022)
Purpose: The compound quinazoline Q-Br, 3-(5-bromo-2-hydroxybenzylideneamino)-2-(5-bromo-2 hydroxyphenyl) 2,3-dihydroquinazoline-4(1H)-one (Q-Br) was evaluated for its antioxidant capacity and potential hepatoprotectivity against sub-chronic liver toxicity induced by thioacetamide in rats.Materials and Methods: Rats were assigned into five groups; healthy (normal) and cirrhosis control groups were given 5% Tween 20 orally, the reference control group was given a Silymarin dose of 50 mg/kg, and low-dose Q-Br and high-dose Q-Br groups were given a daily dose of 25 mg/kg and 50 mg/g Q-Br, respectively. Liver status was detected via fluorescence imaging with intravenous injection of indocyanine green (ICG) and a plasma ICG clearance test. Liver malondialdehyde (MDA), catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GPx) were also tested. The degree of fibrosis was determined histologically by hematoxylin and eosin and Masson's Trichrome staining. The immunohistochemistry of liver tissue inhibitor of metalloproteinase (TIMP-1), matrix metalloproteinase (MMP-2), and alpha-smooth muscle actin (α-SMA) was performed.Results: Q-Br recorded mild antioxidant capacity, dose-dependent improvement in the liver status, and inhibition of oxidative stress compared to cirrhosis control. Histopathology notified a remarkable reduction in the degree of fibrosis. Immunohistochemistry revealed an obvious low expression of MMP-2 and α-SMA along with a higher expression of TIMP-1 in Q-Br- and Silymarin-treated livers.Conclusion: Q-Br treatment altered the course of toxicity induced by thioacetamide suggesting significant hepatoprotective potential of Q-Br treatment.